Embriogênese somática do mamoeiro hermafrodita UENF/Caliman 01 - Gouvea, Drielly Stephania (2016)
The Somatic embryogenesis is the process of development of embryos from somatic cells. The objective of this work to analyze the growth regulators efficiency in different stages of indirect somatic embryogenesis from in vitro plants of hermaphrodite papaya hybrid UENF / Caliman 01. Leaf discs of these shoots were inoculated in induction (MI): MS basal medium (Murashige, Skoog, 1962) with a total concentration of salts and supplemented with auxins 2,4-dichlorophenoxyacetic acid (2,4-D) (6; 9; 12; 15:18 µM) and 4-chlorophenoxyacetic acid (4-CPA) (19; 22; 25; 28 and 31 µM). The treatments were arranged in a completely randomized design (CRD) with five repetitions, five explants per repetition. The data were submitted to analysis of variance by F test and means were compared by Skott-Knott test at the 5% level of significance. During 90 days of induction, visualized training some somatic embryos formed in friable callus. The concentrations of 2,4-D auxin were inhibitory, occurring only the formation of light-brown callus colored, which were lower than 20% results in the formation of somatic embryos, whereas supplementation with 4-CPA resulted in 96% embryogenic callus for the concentration of 25 µM. The embryogenic calli were transferred to the maturation medium (MM): MS without growth regulators; ABA - abiscísico acid (0,5 µM); ABA (0,5 µM) + CA - activated charcoal (15 g L-1 ); ABA (0,5 xi µM) + CA (30 g L-1 ); ABA (0,5 µM) + PEG - polyethylene glycol (60 g L-1 ) for 30 days. Significant differences were observed among the tested maturation media, a positive reaction to the amount of developed embryos and the effect of each treatment. The maturation medium consisting of 0,5 µM ABA CA + 30 g L-1 was the most efficient in the development of cotyledonary somatic embryos. These mature cotyledon embryos were inoculated in germination (MG): MS without growth regulators; GA3 (0,5 mg L-1 ); GA3 (1,0 mg L-1 ) and GA3 (1,5 mg L-1 ).